Exploring narratives as a tool to manage psychosocial distress in children hospitalised for tuberculosis in the Western Cape, South Africa - October, Caitlin Danielle (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.